Inflammatory myofibroblastic tumor of female genital tract with unusual features and potential diagnostic pitfalls - Zhang, Huibin; Chen, Liyu; Lin, Yuanqing; Lu, Ting; Gao, Yin; Luo, Dan; Xu, Shuxia (Frontiers in Oncology, 2025)
BackgroundInflammatory myofibroblastic tumor (IMT) of the female genital tract is frequently misdiagnosed as uterine leiomyoma or mesenchymal stromal tumors due to overlapping morphological features.Materials and MethodsA total of 25 cases of IMT were collected between 2019 and 2024 and 8 of them were classified as IMT with unusual features. We conducted a retrospective analysis of 8 cases of unusual features IMT, focusing on histopathological features, immunophenotype, molecular alterations, and clinical follow-up.ResultsThe misdiagnosis rate is as high as 62.5%. Among these, 3 patients were initially misdiagnosed as uterine leiomyoma; 1 patient was misdiagnosed as low-grade endometrial stromal sarcoma; 1 patient was misdiagnosed as uterine leiomyosarcoma; and 3 patients remained unclear at initial assessment. The patient ranged from 32 to 67 (mean 43) years. Clinically, all presented with uterine masses. Tumors were either solitary or multiple, ranging from 1.2 to 12 cm. Histologically, these tumors exhibited marked heterogeneity with three predominant types, including leiomyoma-like type, myxoid type, and collagenous sclerosis type. 50% of the patients displayed a combination of two or more histologic subtypes. 2 of 8 (25%) patients presented leiomyoma-like morphology; 25% of patients exhibited prominent spiral arteriole proliferation resembling low-grade endometrial stromal sarcoma; 25% of patients occurring during pregnancy presented significant decidual-like changes; and 12.5% of patients resembled epithelioid leiomyosarcoma, characterized by frequent mitotic figures, severe nuclear atypia, prominent nucleoli, and abundant eosinophilic cytoplasm with epithelioid morphology. Immunohistochemical analysis revealed expression of ALK in 62.5% patients. The complete loss of p16 expression was noted in one patient, who was diagnosed as epithelioid inflammatory myofibroblastic sarcoma (EIMS). ALK gene rearrangements were identified by fluorescence in situ hybridization (FISH) on 62.5% patients. All tested cases were positive for ALK rearrangement. During clinical follow-up, 87.5% of patients followed a benign clinical course; the patient of EIMS developed pulmonary and supraclavicular lymph node metastases and remains living with tumor.ConclusionsEIMS has the ability of invasion and metastasis and presents the abnormal loss of p16. Accurate recognition of IMT with unusual features is crucial for targeted treatment. ALK protein expression and molecular testing play critical roles in diagnosis and differential diagnosis, and lowering the detection threshold to improve sensitivity is urgently needed.